Methods of Teaching Students to use Words with Connotative Meaning in the Text in 5th Grade Mother Tongue Lessons - Maxkamova Guluzroxon (International Journal of Formal Education, 2024)
Imagine you hear the word "home." It might make you think of a cozy place filled with love and warmth, right? But if I say "house," you might just picture a building without those warm feelings. Understanding these differences can help us express ourselves better and connect with others more deeply. In our mother tongue lessons, we’ll learn how to use words with positive connotations to inspire each other, create a friendly classroom atmosphere, and make our writing more colorful and engaging. We’ll practice choosing the right words to share our thoughts and feelings, making our communication more effective and enjoyable.